An ergonomic analysis of commercially available exercise equipment : implications for resistance training and clinical rehabilitation - Scott, Stephen Bryce (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1994)
This study examined the often contrived advertising claims of the manufacturers of variable resistance isotonic machinery. Specifically, the study sought to ascertain whether certain equipment was compatible with musculo-skeletal and perceptual needs and limitations of the human user: that is, to determine whether presently installed eccentric cams, which provide the variable resistance, matched the users force curves. The format of this research was in the ergonomic tradition in which empirical research is not necessarily the primary avenue. Consequently the inter-disciplinary nature of ergonomics required small-scale laboratory- simulation experiments to be conducted in a diverse range of disciplines such as physiology, psychology and biomechanics. It was found that on all five pieces of variable resistance machinery analysed, a mismatch between the force curves and the eccentric cams exist. The cams were redesigned accordingly. The metabolic cost of performing fixed-rate isoinertial lifts was moderate. The psychophysical analysis revealed that perceptual responses indicated that the work was classified as 'light' and only at 30% stress levels do local cues begin to dominate. Based on these findings it was concluded that manufacturers advertising claims in the instances analysed were not well-founded and that variable resistance isotonic machinery should only be used to develop muscular strength and endurance, and do not effectively serve as weight-loss devices.
Keywords: Human engineering -- Case studies; Exercise -- Equipment and supplies -- Evaluation; Isometric exercise -- Evaluation